Pension Literacy For The Teachers and Administration Staff in BPK Penabur Jatibarang - Peter, Peter; Wahyusaputra, Tedy; Iskandar, Dini; Gunawan, Ika; Herlina, Herlina; Martalena, Martalena; Hadianto, Bram (Jurnal Abdimas Prakasa Dakara, 2024)
Financial literacy is the basis for building a wise nation to manage money. As one of this kind of knowledge, pension planning and implementation must be deeply introduced by higher education institutions, as exhibited by their lecturers, to society in service to the community. To support it, the lecturers in the undergraduate management department at the Business Faculty of Maranatha Christian University do it by training teachers and administration staff members of BPK Penabur Jatibarang. Moreover, the community service committee takes seven questions from Luchak and Gunderson (2000), develops them into nine questions with a multiple-choice system, and examines the difference in the percentage of accurate answers (PAA) post and pre-presented materials by the paired sample t-test to evaluate this training. Based on this testing result, the participants can correctly answer more questions after training (63.17%) than before (47.30%), reflecting the zone movement based on Chen and Volpe (1998) from the low level below 60% to the middle level between 60% and 79%. Regarding the long-term implementation, the participants must obtain the money needed for pensions by saving money monthly and investing in assets that can elevate their value, such as marketable securities in the capital market, gold, and hard currency.